Epidemiology for community health nursing: an interactive computer assisted instruction program. - Russell KM; Miller AM; Czerwinska J (Computers in Nursing)
Epidemiology and its application to community health nursing is an essential concept for baccalaureate nursing students. To facilitate student learning, nursing faculty chose to use computer assisted instruction (CAI) as an adjunct teaching-learning strategy. An interdisciplinary team, including nursing content specialists and a computer programmer, produced an interactive CAI that integrated epidemiologic content, community health nursing practice, and learning-theory principles. Contents of the program modules are described, and program strategies used to enhance learning are delineated. Evaluation for the program indicated students (N = 106) believed the content was clearly explained and preferred learning with CAI rather than through textbook reading assignments.